Réindustrialiser les territoires, la revanche des villes petites et moyennes ? - Marjolaine Gros-Balthazard; Magali Talandier (EchoGéo)
After decades of decline, industrial employment has been increasing in Europe and France since 2016. The crises are forcing us to rethink production methods and the economic sovereignty of countries, but also the territorial reconfigurations of reindustrialization. For a long time marked by deindustrialization, are small and medium-sized cities taking their revenge on the metropolises? Are they the drivers of this recent industrial rebound or are they dependent on, or even penalized by, metropolitan dynamics? While the results show that reindustrialization occurs mainly in large urban areas, the analysis reveals the structuring role of small and medium-sized cities, but also rural municipalities within these metropolitan areas. We also show the strategic complementarities that link small and medium-sized cities, their rural hinterland and the metropolises.